How do you solve #2(c + 1) - 3c = 3(3 + 2c)#?

1 Answer
Mar 13, 2016

Answer:

Expand the expressions, simplify, then isolate the variable term on one side and the constant on the other to get: #c=1#

Explanation:

Given
#color(white)("XXX")2(c+1)-3c=3(3+2c)#

Expanding
#color(white)("XXX")2c+2-3c=9+6c#

Simplify
#color(white)("XXX")-c+2=9+6c#

Isolate variable term by subtracting #(6c)# from both sides
#color(white)("XXX")-7c+2=9#

Isolate the constant term by subtracting #(2)# from both sides
#color(white)("XXX")-7c=7#

Solve for #c# by dividing both sides by #(-7)#
#color(white)("XXX")c=1#